Upaya Peningkatan Kemampuan Perawat Dalam Memenuhi Kebutuhan Spiritual Care Pasien Dalam Program Pelatihan In House Training - Ramli, Rachmat; Sima, Yenni; Samila, Samila; Prihatini, Surya; Halmar, Halbina Famung; Mulia, Madepan; Rosmiati, Rosmiati; Hajrah, Fifit; Rahim, Abdul (Barongko: Jurnal Ilmu Kesehatan, 2025)
A nurse must be able to understand each different response from the patient to the suffering they experience and provide appropriate health services in each different response, both ongoing and future. Spiritual care is an activity in nursing to help patients that is carried out through attitudes and actions of nursing practice based on the values ​​of spiritual nursing, namely recognizing human dignity, kindness, compassion, serenity and gentleness. The purpose of this study was to improve the knowledge and skills of nurses in providing spiritual nursing care. The research method was patient spiritual care in an in-house training program. Results There was an increase in the knowledge and skills of nurses after participating in the activity. The conclusion shows that In-House Training can improve the knowledge and skills of nurses about spiritual nursing care.